(untitled) (Conversatoria Linguistica, 2022)
The author takes a closer look at the poetic activity of Tadeusz Łada-Zabłocki, who, while in exile, passionately and courageously cultivated literary activity. Presenting an impressive portrait of the exiled poet, she focuses not only on his literary life, but also on his translation work, as a translator of, among other things, communal songs of Transcaucasian Tatars. Łada-Zabłocki is also seen as a protector, promoting young Polish poets and facilitating the publication of their poems.